Identification of bacterial biofilm and the Staphylococcus aureus derived protease, staphopain, on the skin surface of patients with atopic dermatitis - Sonesson, Andreas (2017)
Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by an impaired epidermal barrier, dysregulation of innate and adaptive immunity, and a high susceptibility to bacterial colonization and infection. In the present study, bacterial biofilm was visualized by electron microscopy at the surface of AD skin. Correspondingly, Staphylococcus aureus (S. aureus) isolates from lesional skin of patients with AD, produced a substantial amount of biofilm in vitro. S. aureus biofilms showed less susceptibility to killing by the antimicrobial peptide LL-37 when compared with results obtained using planktonic cells. Confocal microscopy analysis showed that LL-37 binds to the S. aureus biofilms. Immuno-gold staining of S. aureus biofilm of AD skin detected the S. aureus derived protease staphopain adjacent to the bacteria. In vitro, staphopain B degraded LL-37 into shorter peptide fragments. Further, LL-37 significantly inhibited S. aureus biofilm formation, but no such effects were observed for the degradation products. The data presented here provide novel information on staphopains present in S. aureus biofilms in vivo, and illustrate the complex interplay between biofilm and LL-37 in skin of AD patients, possibly leading to a disturbed host defense, which facilitates bacterial persistence.